Thhe outcomes book: debate and consensus after the WPA outcomes statement - Harrington, Susanmarie, editor; Rhodes, Keith, editor; Fischer, Ruth Overman, editor; Malenczyk, Rita, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2005)
The WPA Outcomes Statement is important because it represents a working consensus among composition scholars about what college students should learn and do in a composition program. But as a single-page document, the statement cannot convey the kind of reflective process that a writing program must undertake to address the learning outcomes described.
Keywords: English language -- Rhetoric -- Study and teaching -- United States; Report writing -- Study and teaching (Higher) -- United States